(untitled) (Bangladesh Journal of Psychology, 2026)
Suicidal ideation among university students continues to be a major global mental health challenge. This study examined the role of perceived interparental conflict and parental and partner rejection in the suicidal ideation among university students in Bangladesh. The sample consisted of 410 university students (219 males and 191 females), aged 18-30 years (M = 21.93, SD = 2.74), who volunteered for the study. Data were collected using the Bangla version of the Children’s Perception of Interparental Conflict Scale, Parental Acceptance-Rejection Questionnaire, Intimate Partner Acceptance Rejection Questionnaire, and Scale for Suicidal Ideation. Data were analyzed using descriptive statistics, independent sample t-tests, bivariate correlations, and multiple regression analyses. The findings revealed that a slightly higher number of female students (22.50%) had suicidal ideation than male students (19.20%). Male students had the following correlations with suicidal ideation: interparental conflict (r = .22, p < .01) and paternal rejection (r = .14, p < .05). Female students had the following significant positive correlations with suicidal ideation: partner rejection (r = .15, p <.05), maternal rejection (r = .19, p <.01), and paternal rejection (r = .16, p < .05). In the male model, interparental conflict emerged as a significant predictor (β = .18, t = 2.36, p < .05, 95% CI [.012, .132]) of suicidal ideation. The relational predictors accounted for a total of 6% (R2 = .06) of the variance in suicidal ideation in males and 7% (R2 = .07) in females. These findings show the importance of family and partnership support for mental health and the prevention of suicidal ideation among university students. Bangladesh Journal of Psychology, Vol. 26(1), June 2026, pp. 61-76